Impacts of industrial agglomeration and energy intensity on industrial eco-efficiency-analysis based on spatial correlation and mediating effect - Zhong, Cheng; Hamzah, Hanny Zurina; Yin, Jin; Wu, Desheng; Cao, Jianhong; Mao, Xiaoming; Zhuang, Qianda (Frontiers Research Foundation, 2022)
As a measuring tool of industrial sustainable development, industrial eco-efficiency works as a link between economic benefit and environmental pressure. Industrial agglomeration and energy have always been considered an important influence factor on industrial eco-efficiency. The Chinese government is facing the challenge of reaching a Carbon Peak by the 2060s, within this context, it is critically important to explore the relationship between industrial agglomeration and industrial eco-efficiency, moreover, energy intensity may play a key role between them, which should not be ignored. Therefore, based on the STIRPAT model, this paper constructs a spatial autocorrelation model (SAC model) to analyze the provincial panel dataset from 2009 to 2018, and it is found that: First, the industrial agglomeration has an inverted N-shaped relationship with industrial eco-efficiency, and industrial eco-efficiency indeed have a positive spatial spillover effect. Second, energy intensity plays a mediating role, industrial agglomeration would affect industrial eco-efficiency through energy intensity. Therefore, it is suggested that the government should introduce differentiated industrial agglomeration policies as well as energy-saving policies. In addition, this paper suggests that policymakers should adhere to consistent industrial sustainable development policies.